Evaluation of glaucoma surgery efficiency (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The choice of the assessment criteria is important to evaluate the glaucoma surgery efficiency. Purpose. To develop a comprehensive assessment and to propose a scoring scale of glaucoma surgery efficiency. A comprehensive system to evaluate glaucoma surgery efficiency was proposed as a ratio of hypotensive effect and safety of operation. Surgical success was defined as complete (IOP ? 15 mmHg without glaucoma medication, reduction in IOP ? 30%); qualified (IOP ? 15 mmHg with glaucoma medication, reduction in IOP from 20 % to 30 %) and poor (IOP > 15 mmHg with glaucoma medication, reduction in IOP to 20 %), considering a number of medications pre- and postoperatively, duration of hypotensive effect, reoperations. Safety of the surgery was evaluated as nature and number of intra- and postoperative complications, particularly those that led to the irreversible lost of visual acuity. The cost of operation, the time of rehabilitation, additional manipulations also should be considered. The scoring scale of efficiency of glaucoma surgery was proposed as follows: 4-6 scores, high efficiency of operation; from 1 to 3 scores, mean efficiency of operations; less than 1 point, the efficiency of operations is low. Conclusion: Unified criteria are essential for an objective evaluation of glaucoma surgery efficacy.  Such success criteria as hypotensive effect and its intensity, number of additional medication, hypotensive effect duration, additional procedures and reoperations, complications and their nature, and vision acuity loss rates need to be considered for unified complex assessment of glaucoma surgery success.